Sistem Pakar Diagnosa Penyakit Jeruk Siam Menggunakan Metode Certanty Factory (CF) Berbasis Android - Fadly, Zulfikar; Prasti, Dianradika; Suparman, Suparman (Universitas Cokroaminoto Palopo, 2024)
The aim of this research is to produce an application that can diagnose diseases in Siamese orange plants using the Android-based Certainty Factory (CF) method. The author uses the Research and Development (R&D) method so that the development of the application can meet quality standards. The development method used is the RAD research and development model. The application was designed using Android Studio 2022 with the Klotin and Java programming languages, creating a database using SQL Lite. Based on the results of designing an expert system application for diagnosing Siamese orange disease using the Android-based Certainty Factory (CF) method, the results of black box testing stated that the application can run well and produce results that are as expected. Then, based on the system feasibility test results, it received a score of 3.6, which means that the system feasibility test results are in the very good category. Based on the results, respondents reviewed all aspects of the questionnaire, 100% of respondents gave positive responses. Thus, responses or respondents to the expert system application for diagnosing Siamese orange disease using the Android-based Certainty Factory (CF) method tend to be positive. Keywords: Certainty Factory, Expert System, Siamese Orange Plant, Android